2009
DOI: 10.1002/pen.21492
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of propylene–ethylene copolymers to high‐density polyethylene

Abstract: The adhesion of some propylene–ethylene (P/E) copolymers to polypropylene (PP) and high density polyethylene (HDPE) was studied in order to compare them with other olefin copolymers as compatibilizers for PP/HDPE blends. A one‐dimensional model of the compatibilized blends was fabricated by layer‐multiplying coextrusion. The microlayered tapes consisted of many alternating layers of PP and HDPE with a thin tie‐layer inserted at each interface. The thickness of the tie‐layer varied from 0.1 to 15 μm, which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…In the thin tie‐layer regime (<2 to 3 μm), G decreased rapidly with decreasing tie‐layer thickness for all the tie‐layers. Two analogous regimes based on the tie‐layer thickness were also observed in PP/HDPE microlayers with elastomeric tie‐layers 18, 19. In these cases, the transition from the thick tie‐layer regime to the thin tie‐layer regime also occurred around 1–2 μm…”
Section: Resultsmentioning
confidence: 60%
“…In the thin tie‐layer regime (<2 to 3 μm), G decreased rapidly with decreasing tie‐layer thickness for all the tie‐layers. Two analogous regimes based on the tie‐layer thickness were also observed in PP/HDPE microlayers with elastomeric tie‐layers 18, 19. In these cases, the transition from the thick tie‐layer regime to the thin tie‐layer regime also occurred around 1–2 μm…”
Section: Resultsmentioning
confidence: 60%
“…Increasing T‐peel strength with increasing adhesive (tie layer) thickness, has also been found and is typically attributed to increasing the absolute amount of dissipated energy in the adhesive layer . The latter has also been observed in multilayer systems with repeat units “PP/tie layer/HDPE” as well as “PP/tie layer/Nylon 6” systems, both with elastomeric tie layers. As far as we know, the effect of increasing T‐peel strength with increasing tie layer thickness has never been shown for biaxially drawn multilayer systems.…”
Section: Resultsmentioning
confidence: 81%
“…Kamdar et al investigated the effect of tie layer thickness on the adhesion of ethylene–octene copolymers to polypropylene using multiflux extrusion to generate a multilayered system and found that tie layer thickness improved the adhesion, especially for thin tie layers. Using the same method, the same increase of adhesion with tie‐layer thickness was found for tie layers between polypropylene and polyamide 6 and for tie layers between propylene‐ethylene copolymers and high‐density polyethylene . However, in these studies, neither the effect of processing temperature nor (biaxial) deformation was considered.…”
Section: Introductionmentioning
confidence: 81%
“…17 Therefore, the average segment length b was determined to be 4.93 Å . By using the w-value determined by Narasimhan et al 10 from the SAXS data, we were able to calculate the interfacial width.…”
Section: Co-extrusionmentioning
confidence: 99%